Financial Behavior, Financial Literacy, and Social Media Influencers as Determinants of Generation Z’s Cryptocurrency Investment Decisions - Mahendra Pratama; Yanda Bara Kusuma2 (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study examines the effects of financial behavior, financial literacy, and social media influencers on Generation Z's cryptocurrency investment decisions within the Cryptowolf community. Unlike previous studies that generally examine these factors separately or in conventional investment settings, this research integrates the three determinants simultaneously in a cryptocurrency-based digital community, thereby providing a more comprehensive explanation of investment decision-making among Generation Z. The study employed a quantitative explanatory design using purposive sampling, while the sample size of 150 respondents was determined using Cochran's formula. Data were collected through structured questionnaires and analyzed using multiple linear regression at a 5% significance level. The findings indicate that financial behavior, financial literacy, and social media influencers simultaneously have a significant effect on investment decisions (F = 63.306; p < 0.001). Partially, financial behavior (t = 2.293; p = 0.023), financial literacy (t = 5.942; p < 0.001), and social media influencers (t = 3.972; p < 0.001) each positively influence investment decisions, with financial literacy emerging as the strongest predictor. The model explains 56.5% of the variance in investment decisions. These findings provide practical implications for financial educators, digital investment communities, and policymakers in designing financial literacy programs and promoting responsible investment behavior among Generation Z